Citra Perusahaan : Kebutuhan Perusahaan Dalam Menjalin Hubungan Dengan Para Stake Holder - Arie Indra Chandra (Jurnal Administrasi Bisnis, 2008)
Without any good quality communication with the community, especially with their costumers, hence the company will face obstacles. These obstacles come up since could be a negative impression into company either their institution or their product or services. Therefore a need to govern a positive image with follows some steps. It also needs to manage a good communication with their stakeholder, such as mass media and non-government (community) organization which are concerned with their product or activities. The core of this act is actually start from the costumer or community and end to the costumer or community. Keywords: Image, image communication, image creation